A Study on Selected Psychophysiological Variables of High School Kho-Kho Players in the Narsinghpur District Between Rural and Urban Areas - A Comparative Study - Das, Pintu; Singh, Mejar (Stallion Journal for Multidisciplinary Associated Research Studies, 2024)
Aim - The present study was to find out a compare the selected psychophysiological variables components of high school kho-kho players in the Narsinghpur District between rural and urban areas. Methodology The present study was conducted on 200 male subjects from selected Individual games namely kho kho. Thirty male players each will be selected who participated in the urban and rural areas from narsinghpur district M.P. The age levels of the subjects were ranged from 14 to 16 years. Statistics- Descriptive statistics were used to describe important characteristics of the data. T- test was used as a statistical tool to compare the psychophysical fitness among inter-university wrestling and judo players. The level of significance was 0.05. Result - The finding reveal that there were significant differences in selected psychophysiological variables between urban and rural players of Narsinghpur district.